A Comparative study on venture capital financing between Bangladesh Venture Capital Limited & BD Venture - Shahjahan, Sanjana Binte (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.